Development trends of local self-government in modern countries - Okujava, Mindia (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
Self-governance institutions of modern European countries have attracted special interest for the last decades. As several foreign authors have me-ntioned, political and economic integration of European countries has led not only to sharing of essential decision-making powers with EU governance bodies but has also attached importance to the regional and local self-governance bodies of EU member states. Despite the wide variety of the self-governance systems in those countries, in the current paper, we will review the common features based on the comparative legal approach, which stress the main trends related to the operation of local self-governance bodies. Among those trends, the aspects of ensuring the participation of citizens in political decision-making through local self-governance are of special importance.